Quercetin (3,3′,4′,5,7-pentahydroxyflavone) complexes with calcium (II) and magnesium(II), its potentiometric and spectrophotometric studies - (:unkn) unknown (My University, 2005)
In this study, the stability constants of the complexes of quercetin formed with calcium(II) and magnesium(II) were determined potentiometrically by using Calvin-Bjerrum and Irving Rossotti methods and by spectrophotometry. The evaluated protonation constants of the ligand were found: logK 1=9.63±0.11 and logK2 = 8.32±013, at the 25°C. For the calcium and magnesium complexes logarithms of the stability constants were found: for Ca : logK=2.91±0.04, and for Magnesium: logK=3.51±0.07. From the results, the components of quercetin-metal complexes are given 1:1 (quercetin:metal ratio) both Ca(II) and Mg(II).
Keywords: Calcium; Constant; Magnesium; Potentiometri; Quercetin; Spectrophotometri; Stability